A Peanut‐Shaped Polyaromatic Capsule: Solvent‐Dependent Transformation and Electronic Properties of a Non‐Contacted Fullerene Dimer. Issue 25 (10th May 2019) - Matsumoto, Kyosuke; Kusaba, Shunsuke; Tanaka, Yuya; Sei, Yoshihisa; Akita, Munetaka; Aritani, Kazushi; Haga, Masa‐aki; Yoshizawa, Michito
Abstract: Synthesis of molecular containers capable of incorporating multiple fullerenes remains challenging. Reported here is that room‐temperature mixing of metal ions with W‐shaped bispyridine ligands featuring polyaromatic panels results in the quantitative formation of a peanut‐shaped M2 L4 capsule. The capsule reversibly converts into two molecules of an ML2 double tube in response to changes in the solvent. Notably, the capsule allows the incorporation of two fullerene molecules into the connected two spherical cavities at room temperature. The close proximity yet non‐contact of the encapsulated C60 molecules, with a separation of 6.4 Å, was revealed by X‐ray crystallographic analysis. The resultant, unusual fullerene dimer undergoes sequential reduction within the capsule to generate (C60 .− )2, C60 .− ⋅C60 2−, and (C60 2− )2 species. Furthermore, temperature‐controlled stepwise incorporation of two C60 molecules into the capsule is demonstrated. Abstract : Peanuts : Room‐temperature mixing of metal ions and W‐shaped bispyridine ligands with polyaromatic panels leads to the quantitative formation of either a peanut‐shaped M2 L4 capsule or an ML2 double tube depending on the solvent identity. The capsule incorporates two fullerene molecules within the connected two cavities with a separation of 6.4 Å. The resultant fullerene dimer shows unusual electronic communication.